Fever of unknown origin caused by infectious diseases in the era of migrant and refugee crisis. Issue 33 (January 2020) - Spernovasilis, Nikolaos; Tsioutis, Constantinos; Markaki, Lamprini; Zafeiri, Maria; Soundoulounaki, Stella; Gikas, Achilleas
Abstract: Concern exists in Europe about the possibility of importation of infectious diseases due to the recent influx of migrants and refugees after 2011. In this retrospective 6-year study, we examined the epidemiology of fever of unknown origin (FUO) in Greece over the past years. Forty-eight patients with classical FUO were included. The proportion of infectious causes of FUO (29.2%) was similar to previous studies in Greece and all infections were endemic to the area. Disease-related mortality was 12.5% and no deaths due to infection were recorded. In conclusion, none of the diagnosed infectious causes of FUO raised concerns about the possibility of imported diseases or pathogens. These results re-inforce the perception that migrants and refugees are not carriers of communicable diseases that can cause public health problems to European countries.